The Metaphoric Process: Connections between Language and Life - Fiumara, Gemma Corradi (London Routledge, 1995)
Metaphor is much more than just a linguistic phenomena, argues Gemma Corradi Fiumara, it is in fact the key process by which we construct and develop our ability to understand the world and the people we share it with.Rationality as understood by philosophers has led to a disembodied view of ourselves in which interaction between life and language has been downplayed. By looking at the metaphoric process - in an interpersonal rather than a formal way - its importance in allowing us access to new worlds of experience is revealed. The metaphoric potential in us all exposes us to the world and initiates our involvement in it.
Keywords: Philosophy; Linguistics